Quantitative easing in the Euro Area - Florian Urbschat; Sebastian Watzka (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2017)
We examine the effects of the Asset Purchase Programme (APP) gradually introduced by the European Central Bank from September 2014 onwards. Studying the short-term reaction of financial markets after APP press releases, we analyse the development of bond yields and spreads around these releases. More precisely, we try to estimate different asset price channels by quantifying the cumulative decrease of spreads and by running event regressions for several Euro Area countries. Focusing on the signalling channel, measured by the OIS rate, and the portfolio rebalancing channel, proxied by the conditional bond-OIS spread, we find that the effects in yield and spread reduction were most pronounced for the announcement on the Public Sector Purchase Programme (PSPP) but declined afterwards for additional announcements. Possible explanations for this are the declining degree to which the ECB surprised markets and the increasingly burdensome institutional set-up of the APP. Moreover, our evidence suggests that portfolio rebalancing had a far larger impact on periphery than core countries' bonds, which supports argument made by Cúrdia and Woodford (2011).
urn:nbn:de:bvb:19-epub-37365-7
Keywords: E43; E44; E52; E58; G14; 330; Large Scale Asset Purchase; Yield curve; Quantitative Easing; APP; Event study